Folate receptor-positive circulating tumor cell count, lymphocyte count and derived neutrophil-to- lymphocyte ratio for diagnosing lung cancer relapse - Wang, Huanrong; Liu, Lei; Yan, Jiaqin; Ma, Wang; Du, Yabing; Zhang, Tengfei (Frontiers in Oncology, 2023)
The folate receptor-positive circulating tumor cell (FR+-CTC) count can be used to improve the diagnosis rate of lung cancer. The lymphocyte count (LC) and blood-derived neutrophil/peripheral lymphocyte ratio (dNLR) are involved in inflammatory processes. Whether the FR+-CTC count combined with the dNLR or LC is helpful for diagnosing lung cancer recurrence is not clear. Sixty-eight patients who were initially diagnosed with lung cancer and received first-line treatment were included. The clinicopathological characteristics, routine blood examination results and CTC examination results of the patients were collected. The role of the complete blood count and FR+-CTC count in lung cancer treatment response and prognosis was analyzed. The FR+-CTC count after treatment was significantly correlated with the T stage (p=0.005). Multivariate analysis showed that the pathological type and FR+-CTC count were independent predictors of disease-or progression-free survival (DFS/PFS) in patients with lung cancer (p=0.010 and p=0.030, respectively). The FR+-CTC count, LC and dNLR predicted the recurrence of lung cancer (sensitivity and specificity of the FR+-CTC count, 69.2% and 71.4%; the LC, 50.0% and 88.5%; and the dNLR, 50.0% and 88.1%, respectively). The FR+-CTC count combined with the LC or dNLR improved the diagnostic rate of lung cancer recurrence (sensitivity and specificity of the FR+-CTC count plus the LC, 53.8% and 90.5%, and the FR+-CTC count plus the dNLR, 73.1% and 73.8%, respectively). When these three indicators were combined to predict lung cancer recurrence, the AUC value was 0.817. The FR+-CTC count combined with the dNLR and/or LC after treatment can improve the diagnostic rate of lung cancer recurrence. A higher FR+-CTC count predicts worse DFS/PFS in patients with lung cancer.